Phonology for Language Learners: A Practical Approach to Improving Pronunciation at the State Islamic University of North Sumatra - Ayu Juniaty Siregar; Dea Nita Aulia; Fitri Miftahul Rizky; Milia Putri; Yani Lubis (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to investigate and overcome language pronunciation problems faced by students at the North Sumatra State Islamic University (UINSU). This research will identify the main challenges in pronunciation faced by students, develop a practical approach based on phonological principles to improve their pronunciation abilities, and improve the quality of language teaching and learning at UINSU through the effective application of phonological methods. This research uses a qualitative method with a case study approach to investigate language pronunciation problems among students at the North Sumatra State Islamic University (UINSU). The findings of this research indicate that students at the North Sumatra State Islamic University (UINSU) still face various challenges in Indonesian pronunciation. The main factors causing this challenge include varying mother tongue backgrounds among students, suboptimal teaching methods, and lack of adequate practice in pronunciation.